SIKAP DAN PEMERTAHANAN BAHASA SASAK PADA MASYARAKAT LOMBOK - Elviana Dewi; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to determine how the attitude and maintenance of the Sasak language in the people of Lombok. Sources of data used are teenagers from Lombok, NTB. This study uses a qualitative approach with collection techniques in the form of observation and interviews. In the discussion topic section and the findings of this study, the people of Lombok NTB still maintain the Sasak language as a means of communication in everyday life. This is done by the people of Lombok as evidence of the attitude and maintenance of the Sasak language as their regional language so that it remains intact and maintains the authenticity of the Sasak language. Keywords: Language Attitude, Language Defense, Sasak Language